A colovesical fistula with a persistent descending mesocolon due to partial situs inversus: A case report. (2017) - Mochizuki, Tetsuya; Tazawa, Hirofumi; Hirata, Yuzo; Kuga, Yoshio; Miwata, Tomohiro; Fukuhara, Sotaro; Imaoka, Kouki; Fujisaki, Seiji; Takahashi, Mamoru; Fukuda, Saburo; Nishida, Toshihiro; Sakimoto, Hideto
Highlights: Colovesical fistula was occered in the extremely rare condition: partial situs inversus with persistent descending mesocolon (PDM). Distinctive features of PDM were shortening adhesions noted at the dorsal aspect of the descending and sigmoid mesocolon without marginal vessel. In this case, these congenital abnormalities might help the suture failure during the operation of sigmoid colectomy. Abstract: Introduction: Situs inversus viscerum, a congenital condition in which the visceral organs are a mirror image of their normal physiological positions, could be total or partial. Persistent descending mesocolon (PDM) is a congenital anomaly that is asymptomatic because of its short length. PDM causing intestinal obstruction is a known clinical complication. Presentation of case: A 74-year-old woman presented with pneumaturia and enteruria for two months, and recurrent cystitis for a month. An enhanced computed tomography (CT) showed air in the bladder along with sigmoid colonic diverticula adherent to it, suspecting a fistula. The CT also showed partial situs inversus with the common hepatic artery, and left colic artery arising abnormally from the superior mesenteric artery (SMA). Minimally invasive endoscopic closure using the over-the-scope clipping system was difficult because of thickening and scar tissue due to chronic inflammation from diverticulitis. Thus, a sigmoidectomy was performed to close the fistula. Intraoperatively, we noted an abnormally fixed descending mesocolon. An emergency reoperation was performed on the sixth postoperative day owing to an anastomotic leak. Suture failure was attributed to these congenital abnormalities due to insufficient blood flow from an absent marginal vessel and a high endocolonic pressure by adhesions. Sigmoid colon re-resection and maturation of an ileostomy was performed. The patient had no specific postoperative complications, and the ileostomy was closed after three months. Conclusion: We report an extremely rare case of colovesical fistula due to a PDM in a patient having partial situs inversus with abnormal branches originating from the SMA.